Mental Health Underutilization by Palestinian-Arabs in Israel: Stigma-Related, Attitudinal, and Instrumental Barriers. (June 2023) - Abo-Rass, Fareeda; Abu-Kaf, Sarah; Matzri, Dvir; Braun-Lewensohn, Orna
Background: Many studies show that members of minority groups underutilize mental health services and report more barriers to such utilization than majority groups. However, very little is known about these barriers and their relation to mental health service use among the Palestinian-Arab minority in Israel. Aims: This study examined barriers to mental health service use in this population based on the stigma-related, attitudinal, and instrumental barriers dimensions of the Barriers to Care Evaluation scale (BACE v3) and its correlates to mental health service use. Methods: The participants were a convenience sample of 231 Palestinian Arabs. They completed measures of BACE v3, mental health service use, and sociodemographic characteristics. Results: The findings showed that participants who reported using mental health services had lower levels of barriers in all dimensions compared to those who did not use such services. Attitudinal barriers were found to be the main determinants of mental health service use. Conclusions: This study underscored the role of attitudinal barriers to the utilization of mental health services. The findings indicated that interventions addressing such barriers might be helpful in increasing mental health service use among the Palestinian-Arab minority in Israel as well as other minorities in Israel and elsewhere, who might share similar backgrounds and perceptions.